Efficiency of single-pulse laser fragmentation of organic nutraceutical dispersions in a circular jet flow-through reactor - Friedenauer, Tina; Spellauge, Maximilian; Sommereyns, Alexander; Labenski, Verena; Esatbeyoglu, Tuba; Rehbock, Christoph; Huber, Heinz P.; Barcikowski, Stephan (Beilstein Journal of Nanotechnology, 2025)
Nutraceuticals provide health benefits and particularly profit from a sensitive, high-purity production process. Microparticle laser fragmentation in liquids is an emerging technique for the contamination-free comminution of organic drugs and nutraceuticals aiming at solubility enhancements. However, current discontinuously operated fragmentation setups suffer from chemical degradation by multipulse laser excitation at high fluence and do not allow for systematic studies of the fragmentation mechanisms. In this work, continuous-flow microparticle laser fragmentation in liquids with ultrashort-pulsed lasers was studied in a circular jet reactor using curcumin and cannabidiol as model substances and single-pulse-per-volume element conditions to compare the fragmentation efficiency for these two nutraceuticals. Fragmentation efficiency based on the yield of submicrometer particles and nanoparticles was quantified using UV–vis extinction spectroscopy, scanning electron microscopy, and analytical centrifugation, while high-performance liquid chromatography determined degradation. We found improved fragmentation efficiency at lower mass concentrations. In all experiments, chemical degradation was minimal (<2%), and increased mass concentration of curcumin enabled ultralow by-product formation of 0.01%. The process selectivity against degradation was defined by the application-relevant descriptor of mole degradation per produced submicrometer particle surface and quantified regarding feedstock mass concentration and nutraceutical type. Cytotoxicity in HepG2 cancer cells was significantly reduced in cells treated with laser-processed curcumin in comparison to unirradiated curcumin controls, and antioxidant effects were proven, ensuring high viability even at high curcumin concentrations.
Keywords: antioxidant; cannabidiol; curcumin; drug; food additive; low degradation; nanoparticle; pulsed laser ablation in liquids; solubilization